Differences in the use of telephone and video telemedicine visits during the COVID-19 pandemic - Rodriguez, Jorge A; Betancourt, Joseph R; Sequist, Thomas D; Ganguli, Ishani (The American journal of managed care, 2021)
The coronavirus disease 2019 (COVID-19) pandemic forced health systems to offer video and telephone visits as in-person visit alternatives. Although video visits offer some benefits compared with telephone visits, they require complex setup, which may disadvantage some patients due to the "digital divide." Our objective was to determine patient and neighborhood characteristics associated with visit modality. This was a cross-sectional study across 1652 primary care and specialty care practices of adult patients at an integrated health system from April 23 to June 1, 2020. We used electronic health record and administrative data. Our primary outcome was visit modality (in-person, video, or telephone), which was captured using billing codes. We assessed predictors of using video vs telephone using multivariable logistic regression. We used hierarchical logistic regression to determine the contribution of patient-, physician-, and practice-level components of variance in the choice of video or telephone visits. We analyzed 231,596 visits by 162,102 patients. Sixty-five percent of the visits were virtual (31.7% telephone, 33.5% video). Patients who were older than 65 years (adjusted odds ratio [AOR], 0.41; 95% CI, 0.40-0.43), Black (AOR, 0.60; 95% CI, 0.57-0.63), Hispanic (AOR, 0.76; 95% CI, 0.73-0.80), Spanish-speaking (AOR, 0.57; 95% CI, 0.52-0.61), and from areas with low broadband access (AOR, 0.93; 95% CI, 0.88-0.98) were less likely to use video visits. Practices (38%) and clinicians (26%) drove more of the variation in video visit use than patients (9%). Telemedicine access differences may compound disparities in chronic disease and COVID-19 outcomes. Institutions should monitor video visit use across demographics and equip patients, clinicians, and practices to promote telemedicine equity.